Challenges and Problems Faced by EFL Teachers in Teaching Allomorph through Narrative Text - Inkarizki Swedianisa Amalia; Slamet Setiawan; Syafi’ul Anam; Oikurema Purwati (Vivid: Journal of Language and Literature, 2022)
The fact that teaching English in Indonesia is still driven by textbooks makes not many students have the ability to communicate in English and even they often experience mispronunciation. This study was conducted to find out how to teach allomorphs as a provision to strengthen knowledge of English pronunciation. In addition, this study also seeks to reveal how the challenges faced by EFL teachers in the Allomorph learning process. There are 3 stages that the teacher can do to teach allomorphs through narrative texts; introduction to phonetic symbols, reading the text, and analyzing and practicing the types of allomorphs. From the use of the selected narrative text, it reveals 3 types of allomorphs from 4 types that have been introduced to students in the form of past tense, plural number, and regular possessive. Some of the challenges and problems faced by EFL teachers in teaching English pronunciation, especially allomorphs, is the lack of student motivation to learn. In addition, EFL teachers still hold on to the old philosophy about the lack of importance of learning pronunciation, making this teaching even more difficult. The lack of class hours and the large number of students in EFL classes are also challenges for teachers.